Varieties of Young Children’s Prosocial Behavior in Zambia: The Role of Cognitive Ability, Wealth, and Inequality Beliefs - Chernyak, Nadia; Harvey, Teresa; Tarullo, Amanda R.; Rockers, Peter C.; Blake, Peter R. (Frontiers in Psychology, 2018)
By the third year of life, children engage in a variety of prosocial behaviors, including helping others attain their goals (instrumental helping), responding to others’ emotional needs (comforting), and sharing resources (costly giving). Recent work suggests that these behaviors emerge during the first two years of life (Dunfield & Kuhlmeier, 2013; Svetlova, Nichols, & Brownell, 2010; Thompson & Newton, 2012). To date, however, work investigating early varieties of prosocial behavior has largely focused on Western samples and has not assessed the impact of poverty and inequality. In this work, we investigate prosocial behavior in 3-year-olds in Zambia, a lower-middle income country with high wealth inequality. Experiments were integrated into a larger public health study along with both objective and subjective (parent) measures of wealth and inequality. Three-hundred-seventy-seven children (Mean age = 36.77 months; SD = 2.26 months) were presented with an instrumental helping task, comforting task, and two steps of a giving task – one with higher cost (children could give away their only resource) and one with lower cost (children had 3 resources to give). As predicted, rates of prosociality varied hierarchically by the cost of the action: instrumental helping was the most common followed by comforting, lower cost giving, and higher cost giving. All prosocial behaviors were significantly correlated with one another (with the exception of high cost giving), and with general cognitive ability. Objective family wealth did not predict any of the child’s prosocial behaviors. However, subjective beliefs showed that mothers who believed that they had more than others in their village had children who were more likely to engage in instrumental helping, and mothers who believed that village inequality was a problem had children who were more likely to engage in low cost giving. Low cost giving was also more likely for children whose parents reported reading storybooks to them. This suggests that costly giving in the context of pretend play may relate to children’s experience with using stories as representations of real life events. The results suggest both cultural differences and universalities in the development of prosociality and point to environmental factors that influence prosociality.